Sociality and self-awareness in animals - Lei, Yanyu (Frontiers in Psychology, 2023)
Recognizing one’s mirror reflection appears to be a simple task, but beyond humans, few animals have demonstrated this capability. Mirror self-recognition is indicative of self-awareness, which is one’s capacity for self-directed knowledge. This theoretical paper examines literature from the past 50 years regarding self-recognition in over 30 species. Animals are classified based on the quantity and quality of research supporting evidence of their self-recognition abilities. Additionally, animals are classified as either social or solitary. It was found that only social animals have consistently demonstrated self-recognition, while solitary species studied so far do not seem to possess this trait. This finding aligns with the social intelligence hypothesis. This paper also reveals a lack of research on solitary species and recommends future studies examine self-recognition in these animals. A meta-analysis quantifying sociality on a numerical scale is also recommended. Given the existing evidence, this article proposes that social animals are more likely to be self-aware than solitary species.